Association Between Patent Foramen Ovale and Overt Ischemic Stroke in Children With Sickle Cell Disease - Galadanci, Najibah A.; Johnson, Walter; Carson, April; Hellemann, Gerhard; Howard, Virginia; Kanter, Julie (Frontiers in Neurology, 2021)
Ischemic stroke is one of the most devastating complications of sickle cell anemia (SCA). Previous studies have shown that intracardiac shunting including patent foramen ovale (PFO) can be a potential risk factor for stroke in children with SCA. This study investigates the association between PFO and overt ischemic stroke in the DISPLACE (Dissemination and Implementation of Stroke Prevention Looking at the Care Environment) study cohort of 5,247 children with SCA of whom 1,414 had at least one clinical non-contrast transthoracic echocardiogram. Presence of PFO was taken from the clinical report. Further, we assessed the association between PFO and other clinical and hemolytic factors in children with SCA such as history of abnormal sickle stroke screen [elevated Transcranial Doppler ultrasound (TCD) velocity] and patient's baseline hemoglobin. In 642 children for whom all data were available, the adjusted odds ratio (OR) for overt stroke was higher in those with PFO but this was not statistically significant (OR: 1.49, 95% CI: 0.20–11.03, p = 0.6994). With an OR of 0.85, the study suggested less PFOs in those with abnormal TCD, but this was not statistically significant (95% CI: 0.17–4.25, p = 0.8463). Overall, the prevalence of PFO in this large sub study of non-contrast echocardiography amongst children with SCA is much lower than previous smaller studies using bubble contrast echocardiography. Overt stroke was non-statistically more common in children with SCA and PFO, but there was no evidence that PFO was more common in those with abnormal TCD, the most important pediatric sickle stroke screen.